Analisis Profil Usaha Angkringan Sop Buah Durian Raja Medan - Fitri Rorizki (STIT Sirojul Falah Bogor, 2023)
In terms of raw materials, capital, labor, production, business management, and the amount of profit made, this study seeks to identify and assess the business profile of angkringan soup raja fruit in Medan. In December 2022, the study was done for a month. The information used was both primary and secondary, collected through interviews with the proprietor of the fruit soup company and descriptively examined in the form of tables and figures. According to the research's findings, the Medan Durian Fruit Soup Company is an angkringan, or small firm, with its own capital, 2 employees, and a primary product category of beverages. Fruit soup is the most popular beverage, followed by juice and ice. Consumers most frequently requested iced durian compote, mixed durian fruit soup, and guessed ice koteng banana compote among these beverage categories. Fruits are the primary raw ingredients. Producing daily, with the bulk of customers eating there as well as some ordering takeout or delivery. based on analytical findings for the month of December 2022.